IMPROVING UNIVERSITY STUDENTS’ ENGLISH PROFICIENCY WITH DIGITAL STORYTELLING - Mirza, Hanadi S (International Online Journal of Education and Teaching, 2020)
The purpose of this study is to investigate whether students of English as a foreign language (EFL) at the Lebanese University (LU) can effectively improve their language proficiency by creating digital stories. To do so, the researcher introduced digital storytelling (DST) as an optional assignment in an EFL communication course offered at LU in the fall of 2017-2018. Participants were 20 second-year student-teachers majoring in EFL education. After the completion of their individual or group digital storytelling projects, all the 16 videos were uploaded on the researcher’s YouTube channel and shared on Facebook and WhatsApp. Participants then answered open-ended survey questions about their experience working on DST. Results show that most participants found the activity enjoyable and educational and were eager to repeat their experience, in spite of the technical difficulties they faced. Many participants also reported having gained more self-confidence and improved their Pronunciation, organizational, technical and research skills, as well as their ability to deliver presentations. The majority of participants found the social aspect of DST highly rewarding and enjoyed sharing their work online with their friends and other English-speakers globally. The positive outcomes of this study suggest that DST should be included in the curriculum of university-EFL communication courses.